Implementasi Pendidikan Agama Islam dalam Konteks Multireligius: Studi Kasus di SMA Semen Gresik - Achmad, Nur Syahidah; Yenuri, Ali Ahmad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study aims to describe the implementation of Islamic Religious Education (IRE) in a multireligious school environment, with a case study at SMA Semen Gresik. This qualitative research employed a case study approach through observation, interviews, and documentation. The findings reveal that the implementation of IRE at SMA Semen Gresik is effective and inclusive through three approaches: directive, participatory, and constructive. The application of Islamic values in school life extends beyond the cognitive domain to include affective and psychomotor aspects, as reflected in students’ attitudes of tolerance, cooperation, and respect for differences. The school has successfully fostered a harmonious learning environment without discrimination against non-Muslim students, through inclusive religious instruction, the provision of worship facilities for all religions, and the active involvement of all students in social and religious activities. This demonstrates that Islamic Religious Education can serve as an effective medium to promote moderation and tolerance amid religious diversity in schools.